2021
DOI: 10.1080/21655979.2021.2005217
|View full text |Cite
|
Sign up to set email alerts
|

miR-543 impairs breast cancer cell phenotypes by targeting and suppressing ubiquitin-conjugating enzyme E2T (UBE2T)

Abstract: Breast cancer, with high morbidity worldwide, is a threat to the life of women. MiR-543 was identified as playing an active part in the development of breast cancer involving multiple molecules. The goal of this study was to explore the molecular mechanisms of the involvement of miR-543 in the development of breast cancer. Quantitative real-time PCR (qRT-PCR) or Western blotting was used to detect mRNA or protein expression. Cell counting kit-8 (CCK-8), and the 5-bromo-2ʹ-deoxyuridine (BrdU), wound healing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In conclusion, this study demonstrated that SNHG10 and miR-302b are downregulated in TNBC [ 34 , 35 ]. Overexpression of SNHG10 may serve as a potential target to treat TNBC by upregulating miR-302b through methylation, thereby increasing the sensitivity of TNBC cells to doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study demonstrated that SNHG10 and miR-302b are downregulated in TNBC [ 34 , 35 ]. Overexpression of SNHG10 may serve as a potential target to treat TNBC by upregulating miR-302b through methylation, thereby increasing the sensitivity of TNBC cells to doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro antitumor activity of AG@BSP-VES was evaluated by MTT assay, the fluorescent live/dead ( 33 ) and the scratch wound assay ( 34 ). For the MTT assay, CT26 cells were initially inoculated into a 96-well plate at a density of 5×104/mL.…”
Section: Methodsmentioning
confidence: 99%
“…miR-543 directly targeted UBE2T, and a negative correlation between miR-543 and UBE2T was observed in BrC tissues. In addition, overexpression of miR-543 disrupted the cancer-promoting effects of UBE2T by inhibiting the activity of the ERK/MAPK signaling pathway, thus inhibiting the viability, proliferation, migration and invasion of BrC (95).…”
Section: Expression Of Ube2t In Cancermentioning
confidence: 99%